2023
DOI: 10.2147/jbm.s390666
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin Levels and Other Associated Parameters with Diabetes Mellitus in Adult Patients Suffering from Beta Thalassemia Major

Abstract: Background Although beta thalassemia major (BTM) patients are properly treated with blood transfusions in accompany with iron chelation therapy, they suffer from complications, such as diabetes mellitus (DM). Purpose The purpose was to detect the critical serum ferritin level and other parameters correlated with DM among adult BTM patients. Also, it was to study whether each of these parameters is associated with a certain period of age. Patients and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In Table 1, the prevalence of DM in β-thalassemia is reported and varies from 0% to 35% [10][11][12][13][14][15]. Risk factors for impaired glucose metabolism include older age, high body mass index (BMI), elevated mean ferritin serum levels, and history of splenectomy [11,12,[16][17][18]. Impaired insulin secretion due to iron deposition in the pancreas, insulin resistance, iron-induced fatty acid oxidation with a subsequent decrease in glucagon usage rate, and zinc deficiency contribute to the pathogenesis of DM in β-thalassemia [4,[19][20][21][22].…”
Section: Impaired Glucose Metabolism and Diabetes Mellitusmentioning
confidence: 99%
“…In Table 1, the prevalence of DM in β-thalassemia is reported and varies from 0% to 35% [10][11][12][13][14][15]. Risk factors for impaired glucose metabolism include older age, high body mass index (BMI), elevated mean ferritin serum levels, and history of splenectomy [11,12,[16][17][18]. Impaired insulin secretion due to iron deposition in the pancreas, insulin resistance, iron-induced fatty acid oxidation with a subsequent decrease in glucagon usage rate, and zinc deficiency contribute to the pathogenesis of DM in β-thalassemia [4,[19][20][21][22].…”
Section: Impaired Glucose Metabolism and Diabetes Mellitusmentioning
confidence: 99%
“…Although diabetes is a multi-factorial disease, iron overload is a primary contributing factor. Several studies have shown excessive iron deposition in pancreatic β-cells in β-thalassemia major patients undergoing frequent blood transfusion and iron chelation therapy [24]. Therefore, better management of iron overload in β-thalassemic/pre-diabetics may reduce the risk or delay the onset of diabetes in this patient group.…”
Section: Prevalence Of Diabetes In β-Thalassemia Patientsmentioning
confidence: 99%
“…Assim, as alfas globinas se agregam de maneira que danificam as hemácias, causando hemólise. Como consequência os indivíduos apresentam quadros de anemia e consequentemente fadiga, falta de ar, fraqueza, dores de cabeça e até hepatoesplenomegalia, ou retardo de crescimento, problemas cardíacos, alterações pancreáticas e diabetes (Forni et al, 2023;Ibrahim et al, 2023). Indivíduos portadores de beta talassemia apresentam formas clinicamente significativas e que variam de acordo com as mutações primárias deste indivíduo.…”
Section: Introductionunclassified